Natural Melanin-Based Nanoparticles With Combined Chemo/Photothermal/Photodynamic Effect Induce Immunogenic Cell Death (ICD) on Tumor - Liu, Ding; Huang, Huilin; Zhao, Bingxia; Guo, Weihong (Frontiers in Bioengineering and Biotechnology, 2021)
Melanin, as a natural product, has been used as an extraordinary ingredient for nanomedicine due to its great biocompatibility and light responsive property. In this study, polydopamine (PDA), an analog of melanin, was extracted from dopamine and encapsulated with doxorubicin (DOX). The as-prepared nanoparticles (NPs) with good stability, great biosafety and high near infrared (NIR) responsive property ameliorated the cell uptake of DOX in OS-RC-2/ADR cells, exhibited synergistic chemo/photothermal (PTT)/photodynamic (PDT) effects, induced the release of damage associated molecular patterns (DAMPs), and finally, led to immunogenic cell death (ICD). In general, it was suggested that PDA-DOX NPs with NIR irradiation could serve as a promising agent for tumor therapy.